2003
DOI: 10.1097/01.blo.0000076800.53006.c9
|View full text |Cite
|
Sign up to set email alerts
|

Residual Challenges After Healing of Congenital Pseudarthrosis in the Tibia

Abstract: The purpose of the current study was to evaluate the clinical results of the Ilizarov bone transport method in the treatment of congenital pseudarthrosis in the tibia. In seven patients operated on between 2.6 and 7.8 years of age, primary healing of the pseudarthrosis was achieved in all patients (after additional bone grafting in two patients). Within a followup of 6 to 8 years, major complications occurred in all patients. Five refractures occurred, and in one patient the refracture did not heal. At the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…Procurvatum in the tibia is a characteristic of the disease, but it seems challenging to adequately address all deformities in CPT, especially when considering the fact that patients often weight bear for a few years on the affected limb before primary surgery with resulting adaptations in the foot. Our findings on the residual deformities in CPT confirm those of other authors [17,26].…”
Section: Discussionsupporting
confidence: 93%
“…Procurvatum in the tibia is a characteristic of the disease, but it seems challenging to adequately address all deformities in CPT, especially when considering the fact that patients often weight bear for a few years on the affected limb before primary surgery with resulting adaptations in the foot. Our findings on the residual deformities in CPT confirm those of other authors [17,26].…”
Section: Discussionsupporting
confidence: 93%
“…Its review of the 120 published CPT cases using the Ilizarov technique showed satisfactory results with pseudarthrosis healing in 94 patients [6]. However, Kristiansen [14] emphasized the high complication rate, including residual axial deformities and refracture.…”
Section: Discussionmentioning
confidence: 99%
“…Among these procedures, the Ilizarov technique has a high rate of fusion, allowing for the correction of axial malalignment and leg shortening at the same time [1][2][3][4][5]. The drawback of this technique is its lack of protection against refractures after removal of the fixator [14]. To address this issue, we have developed an original surgical technique that combines Ilizarov's fixator with intramedullary nailing of the tibia.…”
Section: Introductionmentioning
confidence: 99%
“…Although surgical intervention has achieved substantial improvements in terms of the healing rates of congenital pseudarthrosis of the tibia over recent decades, challenging problems still jeopardize the function of the affected limb 2 .…”
mentioning
confidence: 99%